Indexes of Psychological Readiness of Personality to the Extreme Terms of Vital Functions - H. Miroshnichenko (Ukrainian Antarctic Journal, 2014)
In the article the questions of research of psychological readiness of winterers of the Ukrainian Antarctic station of Akademik Vernadskiy are examined to execution of professional duties, the role of account of indexes of psychological readiness of personality is underlined in adaptation to the extreme terms of vital functions.